Indikationen zur urodynamischen Untersuchung = Indication for urodynamic testing - Bross, Stephan (Der Urologe, 2015)
Background: The aim of urodynamic testing is to obtain objective information regarding urinary bladder storage and voiding function. Basic investigations provide information of the underlying incontinence form. Depending on the individual situation and findings, further urodynamic investigations are helpful or indicated. Prior to conservative therapy, a routine urodynamic investigation is not indicated. Objectives: Due to limited evidence of preoperative urodynamic investigations on postoperative results, the urodynamic results may be helpful when considering various treatment options. Results: Urodynamic investigations should be performed preoperatively, especially in case of overactive bladder symptoms, prior incontinence surgery, or disordered bladder emptying. The assessment of urethral function should be considered in the urodynamic investigation of stress urinary incontinence. In patients with pelvic prolapse, urodynamic investigations should be performed during prolapse reposition.